Business incubator management and entrepreneur collaboration with R&D milieus: Does the regional context matter?. (February 2022) - Aarstad, Jarle; Jakobsen, Stig-Erik; Foss, Lene
We study whether business incubator management collaboration with R&D milieus affects incubated entrepreneurs to also collaborate with R&D milieus in different regional contexts. Empirically, we analyse 281 Norwegian entrepreneurs in 32 different business incubators. Incubator collaboration with R&D milieus increases entrepreneur collaboration with R&D milieus in sparsely but not densely populated regions. Also, education level increases collaboration with R&D milieus (plus investor milieus and international customers). Entrepreneur collaboration with R&D milieus is positively associated with market orientation and perceptual performance but tends to delay enterprise development.